Making Dementia Matter Through Sound - Marjolein Gysels; Chris Tonelli; Thomas Johannsen (Voices)
This paper investigates the working practices of the Genetic Choir and the “Stem&Luister” project, in which the ensemble uses voice, sound and improvisation to explore and develop ways of connecting with people with dementia, thereby seeking to improve the experience of care. Their musical sessions are multilayered. First, through listening they develop a sense of the people and the environment. Then through introducing their vocal practices, they breach the prevailing sonic regime. Second, through immersing the residents in sound-making and singing, they draw on the material and sensorial qualities of sound. This gives access to those who were difficult to reach and offers both an alternative means of communication and enables the recognition of selves. A third layer concerns the strategic use of improvisation, of which the deployment of “ensemble” and “instant composition” are analysed. Recognising the compositional efforts in improvisation shows their work to be a form of design. It facilitates attention to personhood, relations, and diversity. This specific practice appears as an untapped resource for the health and wellbeing of people with cognitive and speech impairments. Theoretically, the findings have implications for the notion of care and provide support from practice to existing neurological evidence of the significance of music as a fundamental faculty for survival and wellbeing.